If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -2x = -5 + -1x Solving 2 + -2x = -5 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + -2x + x = -5 + -1x + x Combine like terms: -2x + x = -1x 2 + -1x = -5 + -1x + x Combine like terms: -1x + x = 0 2 + -1x = -5 + 0 2 + -1x = -5 Add '-2' to each side of the equation. 2 + -2 + -1x = -5 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -5 + -2 -1x = -5 + -2 Combine like terms: -5 + -2 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 3x^2-x=140 | | log(x+3)=log(x-3)+1.5 | | 3x^2+4-7x=0 | | B+63=19 | | -4=p+12 | | ln(x+3)=ln(x-3)+1.5 | | 4tanx=10 | | 8b+3=b | | 16+11h=9h | | 8x+26=4x+2 | | 7y-8=4y+31 | | (7x-68)=(-3+110) | | 6x+26=8x+12 | | 3y+-1=7 | | (3x-10)=(3x-2) | | 3x^2+y^2=4 | | M^2+8+16=0 | | 3y+2ln(x)=4ln(y+7) | | (-3+106)=(7x-64) | | (5x+49)=(3x+57) | | 8sin^2x-7=-2cosx | | 10x+4y=52 | | 10x-4y=52 | | F(9)=4(9)-2 | | 3sint-sint=0 | | cos^10x-sin^10x=1 | | 3x+5x=6x | | sqrt(x+15)+15=-sqrt(x) | | 192/4=x/1 | | 1.79266204420746E-308=0 | | X=-4t+2t^2 | | 75=5x^2-20x |